Barriers to Diagnosis Access for Chagas Disease in Colombia - Mario Javier Olivera; Julián Felipe Porras Villamil; Christian Camilo Toquica Gahona; Jorge Martín Rodríguez Hernández (Journal of Parasitology Research)
Chagas disease is the leading cause of nonischemic cardiomyopathy in Latin America. Timely access to diagnosis and trypanocidal treatment and preventive tools for millions of infected people continues to be a challenge. The purpose of this study was to identify potential barriers for the diagnosis of Chagas disease in Colombia from the perspective of healthcare providers. Using a simultaneous mixed-methods study design, we analyzed trends in access to screening and diagnosis for Chagas disease in Colombia and assessed the national barriers to access. The main barriers to access at the national level included a limited governmental public health infrastructure for the diagnosis of Chagas disease and limited physician awareness and knowledge of the disease. Data indicate that 1.5% of total expected cases based on national prevalence estimates were reported. Few public health laboratories have the capacity to perform complementary tests for the diagnosis of Chagas disease and almost 6 months elapse between the requests of the tests and the confirmation of the disease. This study shows that infected people must overcome a number of barriers to achieve diagnosis. Reducing barriers to early diagnosis of Chagas disease is an important goal in the fight against the disease.